Candida isolates causing candidemia show different degrees of virulence in Galleria mellonella. (15th March 2019) - Marcos-Zambrano, Laura Judith; Bordallo-Cardona, María Ángeles; Borghi, Elisa; Falleni, Monica; Tosi, Delfina; Muñoz, Patricia; Escribano, Pilar; Guinea, Jesús
Abstract: We aim to assess intra- and interspecies differences in the virulence of Candida spp. strains causing candidemia using the invertebrate Galleria mellonella model. We studied 739 Candida spp. isolates ( C. albicans [ n = 373], C. parapsilosis [ n = 203], C. glabrata [ n = 92], C. tropicalis [ n = 53], and C. krusei [ n = 18]) collected from patients with candidemia admitted to Gregorio Marañon Hospital (Madrid, Spain). Species-specific infecting inocula (yeast cells/larva) were adjusted (5 × 10 5 [ C. albicans, and C. tropicalis ], 2 × 10 6 –5 × 10 6 [ C. parapsilosis, C. glabrata, and C. krusei ]) and used to infect 10 larvae per isolate; percentage of survival and median survival per isolate were calculated. According to the interquartile range of the median survival, isolates with a median survival under P25 were classified as of high-virulence and isolates with a median survival over P75 as of low virulence. The median survival of larvae infected with different species was variable: C. albicans ( n = 2 days, IQR <1−3 days), C. tropicalis ( n = 2 days, IQR 1.5−4 days), C. parapsilosis ( n = 2 days, IQR 2−3.5 days), C. glabrata ( n = 3 days, IQR 2−3 days), and C. krusei ( n = 7 days, 6.5−>8 days) ( P < .001). Differences in virulence among species were validated by histological examination (day +1 post-infection) in the larvae infected by the isolates of each virulence category and species. Virulence-related gene expression in C. albicans isolates did not reach statistical significance. We report species-specific virulence patterns of Candida spp. and show that isolates within a given species have different degrees of virulence in the animal model.